Jinan Laetitia's Communication Identity in Building Personal Branding as a Singer-Songwriter - Citrawati; Indria Angga Dianita; Nur Rochimah, Harris Annisari Indah (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aims to analyze Jinan Laetitia's personal branding as a singer-songwriter through the Communication Theory of Identity (CTI) approach by applying eleven characteristics of personal branding, namely authenticity, integrity, consistency, specialization, authority, distinctiveness, relevance, visibility, persistence, goodwill, and performance. The phenomenon that occurs is that communication identity in the Indonesian music industry highlights the importance of communicating identity effectively to influence a musician's career. The method used is descriptive qualitative, with data collection techniques in the form of interviews, observations, and documentation. Key informants include Jinan Laetitia, fans, fellow musicians, music experts, and personal branding experts. The results of the study show that there are findings in Jinan Laetitia's personal branding which is built through her authenticity, consistency, and integrity, this strengthens her image in the music industry, because Jinan is a musician who does not only focus on popularity, but also on her personal qualities and values. This study suggests that emerging singer-songwriters can employ similar strategies to strengthen their personal branding by focusing on authenticity, consistency, and integrity.